1967
DOI: 10.1111/j.1469-8986.1967.tb02739.x
|View full text |Cite
|
Sign up to set email alerts
|

Finger Sweat Print Tape Bands

Abstract: A simple inexpensive technique for obtaining finger sweat prints (FSPs) is described. Evidence for its validity is presented. The method proved approximately equal to a more elaborate procedure in sensitivity to an anticholinergic drug effect. FSP techniques, perhaps, have been technically refined without the compensating gains of increased reliability or validity.DESCRIPTORS: Finger sweat prints, Palmar conductance, Anticholinergic drugs. (D. M. McNair) Address requests for reprints to Douglas M. McNair,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1969
1969
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The two most widely used techniques to assess sweat gland functioning are the skin conductance method [27] and the finger-sweat print method [46]. Skin conductance has been measured using a constant current (10 mA) device connected to Ag/ AgCl electrodes which are attached to the palmar sites of fingers and the forehead skin [27].…”
Section: Sweat Glandsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two most widely used techniques to assess sweat gland functioning are the skin conductance method [27] and the finger-sweat print method [46]. Skin conductance has been measured using a constant current (10 mA) device connected to Ag/ AgCl electrodes which are attached to the palmar sites of fingers and the forehead skin [27].…”
Section: Sweat Glandsmentioning
confidence: 99%
“…In the finger-sweat print method [46], the subject's middle finger is moistened using ferric chloride solution in ethanol, dried, and then placed on a strip of tannic-acid treated chromatography filter paper for 3 minutes. The finger print left on the paper can be compared on the basis of color intensity to a previously constructed scale (0±9 points), obtained with fingers left in contact with strips for different periods of time.…”
Section: Sweat Glandsmentioning
confidence: 99%
“…The finger sweat print (FSP) procedure was essentially that described by McNair, Droppleman, and Kussman (1967). After application of the ferric chloride solution to the tip of a forefinger, I min elapsed before a coated sweat band was attached firmly with a cellophane tape; 2 min later, the band was removed.…”
Section: Sweat Measuresmentioning
confidence: 99%
“…Since several previous studies from this laboratory (AIcNair, Droppleman, & Pillard, 1967;McNair, Droppleman, & Kussman, 1967;and Droppleman' & McNair, 1968), have demonstrated that the FSP technique is sensitive to the anticholinergic effect of atropine sulfate, FSP response to atropine sulfate was selected to compare the relative sensitivities of four FSP durations, 0.5, 1.0, 2.0, and 3.0 min.…”
mentioning
confidence: 99%